QUEM SABE O PRÍNCIPE VIROU UM PERIGO: A RELAÇÃO ABUSIVA EM A MEGERA DOMADA (Muitas Vozes, 2022)
This article discusses the play The Taming of the Shrew, renowned comedy by William Shakespeare, starring a couple whose relationship is, at least, problematic, but rather potentially dangerous. Taking into consideration concepts regarding the “romantic ideal” and healthy relationships, we outline the concept of abusive relationship, supported by the studies developed by McCarry (2010), Markey e Markey (2007) e Postmus, Stylianou e McMahon (2015). By recognizing the abusive relationship as different than the unhealthy one, singularly for its increased degree of violence (any type of violence, be it physical, emotional or psychological), we aim topromote a debate about the relationship between Katherina and Petruchio, focusing on the gender roles and power positions of each party of this relationship. We demonstrate the possibility to perceive this relationship as abusive, since Petruchio controls and blackmails his wife in severalopportunities, including severe deprivations, in a dynamic that is far from a healthy relationship. KEYWORDS: The Taming of the Shrew. Romantic ideal. Abusive relationship.